SEROLOGIC EVIDENCE FOR PARAINFLUENZAVIRUS INFECTION DURING ISOLATION AT SOUTH POLE STATION, ANTARCTICA - PARKINSON, ALAN J.; MUCHMORE, H. G.; McCONNELL, T. A.; SCOTT, L. V.; MILES, J. A. R. (Oxford University Press, 1980)
Two distinct mid-winter outbreaks of respiratory tract illness (RTI) occurred among South Pole Station personnel during the winterover period of 1976. One outbreak began early in May eight weeks after total isolation began, the second occurred in August and September after 20 weeks of complete social isolation. Sequential sera collected from 16 of the 18 subjects wintering at South Pole during 1976 were tested by hemagglutination inhibition for antibody against parainfluenzavirus types 1 and 3. Serologic responses were detected against parainfluenzavirus 1 and 3 antigens during the outbreak that occurred in May, and one subject showed a response to parainfluenzavirus 1 in September. Serologic responses occurred in both symptomatic and asymptomatic subjects and were chronologically compatible with the observed illnesses. Throat swabs collected both routinely during the winter and during each outbreak of illness and maintained at −70 C failed to reveal the causative agent when inoculated into cell culture at the home laboratory the following year. Outbreaks of mid-winter RTI and serologic responses in adult subjects isolated at South Pole Station suggest persistence of parainfluenzavirus in the human adult. Confirmation of this observation will require recovery of the virus during outbreaks of RTI within this isolated community.